Human sperm chemotaxis depends on critical levels of reactive oxygen species - Sánchez, Raúl Oscar (2010)
Objective: To verify whether chemotaxis is in part an oxidative process mediated by reactive oxygen species (ROS). Design: In this prospective study, after removal of seminal plasma, the sperm suspension received no treatment (control), ROS formation by stimulation with phorbol 12-myristate 13-acetate (PMA), antioxidant treatment (with catalase), or PMA stimulus in the presence of catalase. At time zero and after 3 hours of incubation, the percentage of capacitated and oriented spermatozoa and the ROS levels were determined. Setting: Andrology laboratory in a medical research institution. Patient(s): Normal semen was obtained from eight men. Intervention(s): The semen samples were evaluated to determine the effect of ROS production by stimulation with PMA and/or antioxidant treatment (with catalase) on the percentage of capacitated and oriented spermatozoa. Main Outcome Measure(s): The sperm capacitation, chemotaxis and reactive oxygen species were assessed before and after PMA and/or antioxidant treatment. Result(s): Prolonged exposure to high quantities of ROS decrease the sperm chemotactic response, probably because of oxidative damage of the cell. However, this effect may be reduced by the addition of antioxidants like catalase. Conclusion(s): Similar to capacitation, chemotaxis seems to depend on the production of ROS, but in the latter process there may be a critical level of ROS necessary for chemotaxis to occur.